Trajectory planning and tracking control for autonomous lane change maneuver based on the cooperative vehicle infrastructure system. Issue 14 (15th August 2015) - You, Feng; Zhang, Ronghui; Lie, Guo; Wang, Haiwei; Wen, Huiyin; Xu, Jianmin
Highlights: Autonomous lane change maneuver was developed using cooperative strategy. Proposed system can be potential to prevent lane change crashes and thus reducing injuries and fatalities. A trajectory planning method based on polynomial was developed. A trajectory tracking controller with global convergence ability was designed. Simulations and experimental results were presented to validate the method. Abstract: Lane change maneuver is one of the most conventional behaviors in driving. Unsafe lane change maneuvers are key factor for traffic accidents and traffic congestion. For drivers' safety, comfort and convenience, advanced driver assistance systems (ADAS) are presented. The main problem discussed in this paper is the development of an autonomous lane change system. The system can be extended applied in intelligent vehicles in future. It solves two crucial issues – trajectory planning and trajectory tracking. Polynomial method was adopted for describing the trajectory planning issue. Movement of a host vehicle was abstracted into time functions. Moreover, collision detection was mapped into a parameter space by adopting infinite dynamic circles. The second issue was described by backstepping principle. According to the Lyapunov function, a tracking controller with global convergence property was verified. Both the simulations and the experimental results demonstrate the feasibility and effectiveness of the designed method for autonomous lane change.